Determinants of serum 25-hydroxyvitamin D levels in healthy young adults living in the Western Cape, South Africa. Issue 4 (23rd August 2019) - Visser, J; Knight, K; Philips, L; Visser, W; Wallace, M; Nel, DG; Blaauw, R
Abstract : Background: Vitamin D deficiency is fast emerging as a global pandemic. In South Africa few studies have been conducted to determine the vitamin D status of the healthy population. Methods: This prospective study with an analytical component investigated vitamin D status of healthy undergraduate students at two time points (winter and summer) at Stellenbosch University. Serum 25(OH)D was determined, anthropometric measurements taken and dietary vitamin D intake estimated (food-frequency questionnaire). Skin tone was determined (Fitzpatrick skin type classification), and a skin reflectometry device used to measure dermal melanin content. Results: Results of 242 students indicated a mean serum 25(OH)D of 63.80 ± 41.35 ng/ml and a high prevalence of vitamin D sufficiency (88%). Significantly more females experienced suboptimal vitamin D levels than males (18 vs. 5%; p < 0.01). Participants with lighter skin tones had higher levels of 25(OH)D than those with darker skin tones (chi-square = 24.02; p = 0.02). The majority (60.74%) had a normal BMI, although there was no significant relationship between BMI and serum 25(OH)D (Spearman's r = –0.11; p = 0.09). Total mean dietary vitamin D intake was 7.99 ± 13.81 mcg, with 87.2% having inadequate intake (< 15 mcg). The relationship between total vitamin D intake and serum 25(OH)D was found to be significant in winter ( p < 0.001) and summer ( p = 0.01). Serum vitamin D levels were significantly higher in the winter phase ( p < 0.001). Conclusions: A low prevalence of vitamin D deficiency was found amongst healthy young adults, despite low dietary vitamin D intakes. Significant relationships were found between serum 25(OH)D and gender, skin tone and vitamin D intake. Further studies need to be conducted, especially in high-risk groups, before results are applied to the greater South African public.